2014
DOI: 10.1371/journal.pbio.1002009
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Mapping Identifies a New Arsenate Reductase Enzyme Critical for Limiting Arsenic Accumulation in Plants

Abstract: A genome-wide association study identifies the enzyme in plants that transforms arsenate into arsenite, allowing its extrusion into the soil and thereby controlling arsenic accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
207
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(222 citation statements)
references
References 82 publications
(121 reference statements)
10
207
2
Order By: Relevance
“…The currently available large populations, dense genotyping, and the advantage of homozygous lines in the mainly self-fertilizing species Arabidopsis, ought to greatly enhance the power of such studies. Indeed, GWA studies confirmed many of the previously identified genes in experimental mapping populations and mutant studies and detected a number of, to our knowledge, novel candidate genes, although this is limited for quantitative traits (Atwell et al, 2010;Brachi et al, 2010;Li et al, 2010;Todesco et al, 2010;Chan et al, 2011;Chao et al, 2012;Filiault and Maloof, 2012;Sterken et al, 2012;Yano et al, 2013;Chao et al, 2014;Meijón et al, 2014;Bac-Molenaar et al, 2015). Similar to the problem of missing heritability in human GWA studies, where individual variants cannot explain the phenotypic variation despite high heritabilities (Yang et al, 2010;Gibson, 2011;Makowsky et al, 2011), genetic variants cannot fully explain the high heritabilities in plant studies (Brachi et al, 2010;Sasaki et al, 2015).…”
mentioning
confidence: 55%
“…The currently available large populations, dense genotyping, and the advantage of homozygous lines in the mainly self-fertilizing species Arabidopsis, ought to greatly enhance the power of such studies. Indeed, GWA studies confirmed many of the previously identified genes in experimental mapping populations and mutant studies and detected a number of, to our knowledge, novel candidate genes, although this is limited for quantitative traits (Atwell et al, 2010;Brachi et al, 2010;Li et al, 2010;Todesco et al, 2010;Chan et al, 2011;Chao et al, 2012;Filiault and Maloof, 2012;Sterken et al, 2012;Yano et al, 2013;Chao et al, 2014;Meijón et al, 2014;Bac-Molenaar et al, 2015). Similar to the problem of missing heritability in human GWA studies, where individual variants cannot explain the phenotypic variation despite high heritabilities (Yang et al, 2010;Gibson, 2011;Makowsky et al, 2011), genetic variants cannot fully explain the high heritabilities in plant studies (Brachi et al, 2010;Sasaki et al, 2015).…”
mentioning
confidence: 55%
“…Technological advancements have made it possible to characterize the genetic diversity in such collections in great detail. A number of studies have shown the use of such densely genotyped natural populations in GWA mapping approaches (Cockram et al, 2010;Chan et al, 2011;Chao et al, 2014;Verslues et al, 2014). Such studies not only disclose the large amount of natural variation present in species for many traits but also hint at candidate genes causal for the observed variation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that this gene might not be the causal gene, although the wild-type Col-0 allele in itself can already be weak or nonfunctional and additional experiments of knockout and overexpression lines of nonCol-0 alleles of this gene are needed for final determination. Because causal genes are sometimes also detected outside the LD interval of significantly associated SNPs (Chao et al, 2014), due to, among others, low linkage between causal and associated SNPs (Freedman et al, 2011), other genes in the 20-kb region around the significant SNPs (10 kb upstream and 10 kb downstream) were considered as candidates, in accordance to the average linkage distance in Arabidopsis of 10 kb (Kim et al, 2007). This resulted in the identification of a candidate gene, QUASIMODO-LIKE2 (QUL2; Smyth et al (1990).…”
Section: Preanthesis Sensitivity To Heat Stressmentioning
confidence: 99%
“…An alternative explanation for the increased net efflux of As is that knockout of NIP7;1 reduces uptake of AsIII from the medium. The majority of AsV taken up by the plant will be rapidly reduced to AsIII prior to efflux from the root [3,21]. Values are mean concentrations of seed from four individuals of each genotype after growth in 150 lM AsV.…”
Section: Discussionmentioning
confidence: 99%